2019
DOI: 10.3389/fpsyt.2019.00820
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiological and Psychological Mechanisms of Qigong as a Treatment for Depression: A Systematic Review and Meta-Analysis

Abstract: Objective: An increasing number of studies have shown the anti-depressive effect of qigong. However, its underlying mechanism remains poorly understood. This study aims to systematically review and meta-analyze existing literature on the mechanism of qigong in reducing depression. Method: The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomized controlled trials of qigong were searched from PsycINFO, PubMed, Embase, ScienceDirect, and Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…Moreover, a meta-analysis of 23 trials that studied the effects of yoga in patients with T2D revealed that yoga significantly reduced the afternoon, evening, and waking cortisol levels, but did not reduce the 30 or 60 min post-waking and mid-morning cortisol levels, or the cortisol slope [ 93 ]. According to a meta-analysis related to qigong, the cortisol level was not significantly changed [ 129 ]. Therefore, the blood glucose level altered through MBI might be partially contributed to by the cortisol-mediated pathway.…”
Section: Epigenetic Changes Induced By Mind–body Intervention and mentioning
confidence: 99%
“…Moreover, a meta-analysis of 23 trials that studied the effects of yoga in patients with T2D revealed that yoga significantly reduced the afternoon, evening, and waking cortisol levels, but did not reduce the 30 or 60 min post-waking and mid-morning cortisol levels, or the cortisol slope [ 93 ]. According to a meta-analysis related to qigong, the cortisol level was not significantly changed [ 129 ]. Therefore, the blood glucose level altered through MBI might be partially contributed to by the cortisol-mediated pathway.…”
Section: Epigenetic Changes Induced By Mind–body Intervention and mentioning
confidence: 99%
“…A 10-week Qigong training for nursery and midwifery students resulted in reduced depressive mood [ 80 ]. The effectiveness of Qigong in relieving depression has been attributed to a reduction in cortisol levels [ 42 ] and activation of the parasympathetic nervous system [ 81 ].…”
Section: The Role Of Qigong For Recovery and Healthmentioning
confidence: 99%
“…Recently, a number of systematic reviews and meta-analyses have demonstrated the positive impact of TQ on physical conditions such as arthritis [24], cancer [25], diabetes [26], falls prevention [27], fibromyalgia [28], osteoarthritis [29], chronic pain [24,30] and cognitive function [31]. Evidence also supports the psychological benefits of TQ, particularly for symptoms of anxiety and depression [32]. Furthermore, several descriptive reviews have examined the beneficial effects of mind-body interventions, i.e., TQ, yoga and meditation on immune function and immune system-related inflammatory biomarkers [33,34].…”
Section: Introductionmentioning
confidence: 99%